Comparison of ventilator-integrated end-tidal CO2 and transcutaneous CO2 monitoring in home-ventilated neuromuscular patients. (August 2016) - Orlikowski, David; Prigent, Helene; Ambrosi, Xavier; Vaugier, Isabelle; Pottier, Sandra; Annane, Djillali; Lofaso, Frederic; Ogna, Adam
Abstract: Background: Non-invasive transcutaneous capnometry (TcCO2 ) is used to assess the home ventilation's efficiency. Recently, end-tidal CO2 (ETCO2 ) sensors have been integrated in life-support home ventilators. The purpose of this study was to compare the ventilator-integrated ETCO2 with TcCO2, in home-ventilated neuromuscular disease patients. Methods: ETCO2 and TcCO2 were simultaneously measured during one night in 28 patients. Daytime blood gases were drawn on the following morning to measure arterial PCO2 (PaCO2 ). Results: Compared to PaCO2 values, both ETCO2 and TcCO2 showed a small bias (−0.1 mmHg and 0.6 mmHg, respectively) and a similar critical difference (6.8 mmHg and 7.3 mmHg, respectively). We found a good correlation between ETCO2 and TcCO2, both considering the mean nocturnal PCO2 (r = 0.897, p < 0.001; bias −1.1 [− 9.0; 6.9] mmHg) and the maximal PCO2 value over the night (r = 0.905, p < 0.001; bias 3.1 [−4.5; 10.8] mmHg). The concordance of the two techniques in detecting overnight PCO2 fluctuations was high, with r = 0.919 (p < 0.001) for the time spent with PCO2 >45 mmHg and r = 0.943 (p < 0.001) for the time with PCO2 >50 mmHg. Conclusions: The ventilator-integrated end-tidal CO2 monitoring is as reliable as the currently used transcutaneous measurement, resulting to be a valuable proxy of the overnight PCO2 evolution. This result opens the possibility of a simplification in the monitoring of home ventilated patients, since ETCO2 measurement can be performed directly at home, with a low additional cost. However, the accuracy of both these measurement techniques is not sufficient to replace blood gases, which remain the reference examination. ClinicalTrials.gov registration: NCT02068911 . Highlights: Transcutaneous (TcCO2 ) and end-tidal CO2 (ETCO2 ) allow non-invasive CO2 monitoring. Ventilator-integrated ETCO2 is as reliable as the currently used TcCO2 . ETCO2 may allow a simplification in the monitoring of home ventilated patients. The accuracy of both ETCO2 and TcCO2 is not sufficient to replace blood gases.